Fundamental study of glycerol-3-phosphate acyltransferase for understanding the mechanism of lipid synthesis (FRGS15-207-0448) - Ismail, Nur Faiqah; Muhamad Yussoff, Muhamad Ariff; Mohd Ashaari, Mardiana; Mohammad Noor, Normawaty; Abd Halim, Khairul Bariyyah (2019)
GPAT is one of the enzymes that catalyzes the initial step in the TAG biosynthesis pathway, thus it is a promising target for genetic manipulation to increase lipid synthesis. Lipid content and type of fatty acids produced by microalgae are the main factors in determining the potential use of microalgae biomass due to the fact that microalgae lipid has high potential applications in food, biofuels and pharmaceutical industries. A lot of research has been performed on all aspects of microalgae lipid production including the basic research on triacylglycerol (TAG) biosynthesis pathway. Glycerol-3-phosphate acyltransferase (GPAT) is the first enzyme that catalyzes the TAG synthesis. Understanding the lipid profile at different salinity and the structural details of the GPAT enzymes in microalgae is crucial in order to understand its role in lipid synthesis.